Reactivation of mTOR signaling slows neurodegeneration in a lysosomal sphingolipid storage disease - Hongling Zhu; Y. Terry Lee; Colleen Byrnes; Jabili Angina; Danielle A. Springer; Galina Tuymetova; Mari Kono; Cynthia J. Tifft; Richard L. Proia (Neurobiology of Disease)
Sandhoff disease, a lysosomal storage disorder, is caused by pathogenic variants in the HEXB gene, resulting in the loss of β-hexosaminidase activity and accumulation of sphingolipids including GM2 ganglioside. This accumulation occurs primarily in neurons, and leads to progressive neurodegeneration through a largely unknown process. Lysosomal storage diseases often exhibit dysfunctional mTOR signaling, a pathway crucial for proper neuronal development and function. In this study, Sandhoff disease model mice exhibited reduced mTOR signaling in the brain. To test if restoring mTOR signaling could improve the disease phenotype, we genetically reduced expression of the mTOR inhibitor Tsc2 in these mice. Sandhoff disease mice with reactivated mTOR signaling displayed increased survival rates and motor function, especially in females, increased dendritic-spine density, and reduced neurodegeneration. Tsc2 reduction also partially rescued aberrant synaptic function–related gene expression. These findings imply that enhancing mTOR signaling could be a potential therapeutic strategy for lysosomal-based neurodegenerative diseases.